Multiple fault slip triggered above the 2016 Mw 6.4 MeiNong earthquake in Taiwan. Issue 14 (20th July 2016) - Huang, Mong‐Han; Tung, Hsin; Fielding, Eric J.; Huang, Hsin‐Hua; Liang, Cunren; Huang, Chung; Hu, Jyr‐Ching
Abstract: Rapid shortening in convergent mountain belts is often accommodated by slip on faults at multiple levels in upper crust, but no geodetic observation of slip at multiple levels within hours of a moderate earthquake has been shown before. Here we show clear evidence of fault slip within a shallower thrust at 5–10 km depth in SW Taiwan triggered by the 2016 Mw 6.4 MeiNong earthquake at 15–20 km depth. We constrain the primary coseismic fault slip with kinematic modeling of seismic and geodetic measurements and constrain the triggered slip and fault geometry using synthetic aperture radar interferometry. The shallower thrust coincides with a proposed duplex located in a region of high fluid pressure and high interseismic uplift rate, and may be sensitive to stress perturbations. Our results imply that under tectonic conditions such as high‐background stress level and high fluid pressure, a moderate lower crustal earthquake can trigger faults at shallower depth. Key Points: Shallower fault slip was triggered by median size deeper earthquake Ascending and descending InSAR reveals detailed coseismic surface deformation and helps constrain fault slip at different depths Evidence of triggered slip on a shallower duplex thrust structure and this deformation are inferred to be slow or aseismic